A novel magnetic cooling device for long distance heat transfer. (25th January 2022) - Pattanaik, M.S.; Cheekati, S.K.; Varma, V.B.; Ramanujan, R.V.
Graphical abstract: Highlights: A novel 8 m perimeter magnetic cooling device for long distance heat transfer. Cooling of heat load by up to 41 °C by this device. Exhibits cooling over a range of heat flux values. Significant cooling of 17 °C for a 20 m perimeter magnetic cooling device. Thermal boundary layer disruption and fluid vortex leads to enhanced cooling. Abstract: Effective transfer of waste heat is a major challenge in a plethora of industrial and commercial systems and devices. Prolonged operation at elevated temperatures can adversely affect system performance, reliability, and service life. Conventional heat pipes are limited by their heat transport performance limitation at longer device length scales. On the other hand, we show that a magnetic cooling device, based on ferrofluid thermomagnetic convection, can transfer heat over much longer distance. We report the development and performance of an 8 m perimeter racetrack-shaped magnetic cooling device, an order of magnitude longer than conventional heat pipes. The temperature drop at the heat load was up to 41 °C for an initial heat load temperature of 197 °C. Cooling increased for larger heat flux, revealing the self-pumping and self-regulating nature of our device. The local Nusselt number exhibited a maximum near strong magnetic fields, resulting in enhanced cooling. The power transferred from heat load to the heat sink is maximum at higher heat load temperature, whereas the total power loss is minimum. The simulated velocity and temperature profiles revealed vortex formation and disruption of the thermal boundary layer, which also increased cooling. Heat load cooling by 17 °C was predicted even for a 20 m perimeter magnetic heat pipe. Our magnetic cooling device is a ferrofluid-based passive device for long-distance heat transfer, making it attractive for a wide variety of engineering applications.